Implementation of Contextual Teaching and Learning Models to Improve Motivation and Scientific Attitude of Students at SDN Banjarejo - Anggareni, Tika (Al Hikmah: Journal of Education, 2022)
The learning model used by the teacher in the classroom based on the results of the researchers' initial observations is still conventional, student motivation is low and students' scientific attitude is lacking. Teachers need to use a suitable and PAIKEM learning model. The purpose of this study was to determine and analyze scientific motivation and attitudes before and after following the CTL model. The research method is a quasi-experimental design with one group pretest and posttest design techniques. The sample in this study were all fourth grade students at SDN Banjarejo Kendal which consisted of 24 students. Techniques and instruments for collecting data are the psychological scale of students' motivation and scientific attitudes. The data analysis technique used non-parametric statistical tests. The results showed that the students' motivation and scientific attitude before and after following the CTL model were that students experienced significant positive differences. This is reinforced by the results of hypothesis testing 1 and 2, which is the value of below the value of = 5%.